Analysis of the Effect of Marine Currents on an Aerial-Underwater Vehicle - Rodrigues, Kepler E. W.; Brião, Stephanie L.; Pinheiro, Pedro M.; Cunha, Mauro A. B.; Machado, Cláudio L. D.; Drews, Paulo L. J. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
Aerial-underwater vehicles present control challenges in both aerial and underwater environments, so obtaining a model for simulating the current effects experienced by these vehicles in both environments provides an important theoretical basis for analyzing dynamic behavior in closed-loop control. This article proposes the analysis of an aerial-underwater hybrid vehicle while adding the effects of ocean currents as perturbations. In this regard, it is intended to explore two numerical simulation scenarios: in the first scenario, the vehicle performs a mission in an underwater environment without the presence of ocean currents, and in the second scenario, with the inclusion of the effect of ocean currents under the same mission conditions, to illustrate the difference in the vehicle's behavior.